Mitochondria in White, Brown, and Beige Adipocytes - Cedikova, Miroslava; Kripnerová, Michaela; Dvorakova, Jana; Pitule, Pavel; Grundmanova, Martina; Babuska, Vaclav; Mullerova, Dana; Kuncova, Jitka (Stem cells international, 2016)
Mitochondria play a key role in energy metabolism in many tissues, including cardiac and skeletal muscle, brain, liver, and adipose tissue. Three types of adipose depots can be identified in mammals, commonly classified according to their colour appearance: the white (WAT), the brown (BAT), and the beige/brite/brown-like (bAT) adipose tissues. WAT is mainly involved in the storage and mobilization of energy and BAT is predominantly responsible for nonshivering thermogenesis. Recent data suggest that adipocyte mitochondria might play an important role in the development of obesity through defects in mitochondrial lipogenesis and lipolysis, regulation of adipocyte differentiation, apoptosis, production of oxygen radicals, efficiency of oxidative phosphorylation, and regulation of conversion of white adipocytes into brown-like adipocytes. This review summarizes the main characteristics of each adipose tissue subtype and describes morphological and functional modifications focusing on mitochondria and their activity in healthy and unhealthy adipocytes.